(untitled) (Physical Culture and Sport: Scientific Perspective, 2025)
The article highlights the issue of declining physical activity and deteriorating health among men in the second period of adulthood within the context of modern socio-economic conditions. The relevance of the study is substantiated by the widespread prevalence of sedentary lifestyles, high levels of psycho-emotional stress, the presence of harmful habits, and an increase in chronic disease incidence. The purpose of the study was to assess the current level of physical activity among men in the second period of adulthood and to scientifically justify the effectiveness of health-oriented training methods for improving their functional state. A comprehensive set of general scientific and specialized methods was applied, including literature analysis and synthesis, pedagogical testing, questionnaires, biomedical methods, and statistical analysis. The study involved 12 men engaged in regular table tennis training at the “Motor Sich” sports club. To collect data, a specially designed 30-item questionnaire was used, covering aspects of a healthy lifestyle, levels of physical activity, and attitudes toward physical exercise. The results of the questionnaire and initial diagnostics revealed a predominance of intellectual labor among respondents, insufficient physical activity, the presence of harmful habits, excess body weight, and a wide variability in physical fitness. It was found that the majority of respondents recognize the importance of physical activity, quality sleep, and balanced nutrition for maintaining health; however, the actual level of systematic physical engagement remains insufficient. The necessity of implementing individualized health and fitness programs tailored to the age-related, morpho-functional, and psychophysiological characteristics of men in the second period of adulthood is substantiated.